Examining clinical leadership in Kenyan public hospitals through the distributed leadership lens - Nzinga, J; McGivern, G; English, M (Oxford University Press, 2018)
Clinical leadership is recognized as a crucial element in health system strengthening and health policy globally yet it has received relatively little attention in low and middle income countries (LMICs). Moreover, analyses of clinical leadership tend to focus on senior-level individual leaders, overlooking a wider constellation of middle-level leaders delivering health care in practice in a way affected by their health care context. Using the theoretical lens of ‘distributed leadership’, this article examines how middle-level leadership is practised and affected by context in Kenyan county hospitals, providing insights relevant to health care in other LMICs. The article is based on empirical qualitative case studies of clinical departmental leadership in two Kenyan public hospitals, drawing on data gathered through ethnographic observation, interviews and focus groups. We inductively and iteratively coded, analysed and theorized our findings. We found the distributed leadership lens useful for the purpose of analysing middle-level leadership in Kenyan hospitals, although clinical departmental leadership was understood locally in more individualized terms. Our distributed lens revealed medical and nursing leadership occurring in parallel and how only doctors in leadership roles were able to directly influence behaviour among their medical colleagues, using inter-personal skills, power and professional expertize. Finally, we found that Kenyan hospital contexts were characterized by cultures, norms and structures that constrained the way leadership was practiced. We make a theoretical contribution by demonstrating the utility of using distributed leadership as a lens for analysing leadership in LIMC health care contexts, revealing how context, power and inter-professional relationships moderate individual leaders’ ability to bring about change. Our findings, have important implications for how leadership is conceptualized and the way leadership development and training are provided in LMICs health systems.